Analisis Sifat Fisika dan Kimia terhadap Kualitas Air Irigasi Pada Lahan Sawah di Desa Cisarua RT 01 RW 03 Bogor - Chika Shafa Maura; Dewi Nur Lathifa Abdul Rozak; Syawal Adrian Syah; Yunita Sari; Alsifa Andita Putri; Amarisa Nur Affifah; Bella Pricilya Nababan (Risenologi, 2023)
Indonesia is very interested in the existence of water to support the agricultural sector by utilizing water for irrigation. The purpose of this study was to determine the physical and chemical properties of irrigation water quality in rice fields in Cisarua Village RT 01 RW 03 Bogor. The research method is a qualitative descriptive research where this method focuses on in-depth observations and focuses on facts in the field. Samples were taken at 6 irrigation water points on paddy fields. In each predetermined paddy field, water sampling is carried out for quality testing in physical properties (water temperature, color, TDS and odor) and chemically, namely the degree of acidity (pH). The results of the study from point 1 to point 6 of irrigation water in paddy fields successively from temperature tests were 28 °C, 27 °C, 27 °C, 28 °C and 27 °C. Test the color of the six points that are colorless. Test from all six odorless points. pH tests from point 1 to point 6 are 7.4, 7.2, 7.3, 7.3, 7.3, 7.2, 7.1, respectively. Furthermore, the total dissolve solid (TDS) test at points 1 to 6 respectively is 40 ppm, 42 ppm, 42 ppm, 32 ppm, 39 ppm, 23 ppm. So it can be concluded that the quality of irrigation water on paddy fields in Cisarua Village RT 01 RW 03 Bogor is in accordance with the standards of 492 / MENKES / PER / IV / 2010 and PP No. 82/2001.